EFFECTS OF DATURA ALBA NEES LEAVE EXTRACT ON LIPID PROFILE AND ELECTROLYTES PARAMETERS IN MALE WISTAR RATS - Gbaranor K. B; Ovili-Odili, B. Z; Tamuno-Opubo A; Nwoke M. F; Sarone F; Uruaka C. I; Edward U. F; Enebeli K. S; Oriji E. I; Goerge U. A (Western European Studies, 2025)
Lipid profile is an essential parameter that need to be assessed periodically ascertain the levels and ensure that it is within the normal values in other to maintain good health. The aim of the research is to Evaluate The Effects Of Datura Alba Ness Leave Extract On Lipid Profile and Electrolytes Parameters In Male Wistar Rats. 20 rats were randomly selected and placed into four groups with five rats per group. The control group was fed with rodent chow and water, the low dose group was given 500mg/kg/bwt of the extract, medium dose group was given 1000mg/kg/bwt of the extract, the high dose group was given 2000mg/kg/bwt of the extract. All the extracts were given orally. Administration lasted for 21 days and on the 22nd day, animals were weighed and sacrifice, blood samples were collected for lipid profile and electrolytes parameter’s analysis. Data were analysed using ANOVA and SPSS version 25 were used and p < 0.05 was said to be significant. The study shows significant decrease in the chloride levels of the rats administered with both medium and high doses of the extract when compared to the control group. No significant decrease or increase in both potassium and bicarbonate levels. The study shows significant decrease in the chloride levels of the rats administered with both medium and high doses of the extract when compared to the control group. No significant decrease or increase in both potassium and bicarbonate levels. Very low density lipoprotein serum levels significantly increased when low doses of the extract were administered and significantly decrease when medium dose were administered and compared with the control group
Keywords: Effects; Leaves; Extract